DIALEKTOLOGI BAHASA MELAYU DI KABUPATEN LANDAK - ., Patriantoro (MAGISTRA, 2012)
This research discussed the dialectology of Malay used by the people in the coastal area of Landak,particularly those who live in the downstream area of the Kapuas river. Malay has been used by agreat numberof people who reside in the coastal area. This research employs quantitative as well as qualitative researchmethods. The data are collected trought the use of in-depth interview method and elicitation technique bydirectly showing the pictures, pointing the real objects, or explaining the intended activities. The Synchroniccomparative method is used to analyze the dialectology of Malay, and the diachronic comparative method isused to help with the analysis of the language construction. The dialectometry is used to figure the percentageof lexicon differences between the research areas. The top down reconstruction technique serves as the way toanalyze the data to find the retention the innovation forms. The lexicon differences in different areas the arecalculated by applying the triangular or polygons de thiessen. The result of data analysis shows that area 1-2,1-3, 2-3, 2-4, 3-4 hold under 21% of lexicon differences which indicates that they share same and not different.In the areas where the research is conducted, some of the relic from of the proto-language are still found, aswell as the innovation forms and the borrowing.Key words: Synchronic comparative, diachronic comparative, language construction.